Early Nutrition and Its Importance in Poultry: A Review - Prabakar, Govinthasamy; Pavulraj, Selvaraj; Shanmuganathan, Subramaniyan; Kirubakaran, Arumugam; Mohana, Nandan (Indian Journal of Animal Nutrition, 2018)
First few weeks of life after hatching are very important in poultry. Immediate access of chicks to caloric nutrients enhances growth rate, yolk utilization, gastro-intestinal development, immune system stimulation etc.Therefore, overall performance of broilers can be increased. However, early feeding is not practised routinely due to practical aspects like differences in hatching period of different chicks of same batch and time consideration of sorting, sexing and transport of chicks. Further, early feeding may incur additional cost. Studies revealed that early feeding has favourable effect on poultry production by improving yolk utilization,growth rate, development of digestive system and immune system which result in superior performance at marketing with good profit and extra cost of early feeding can be compensated.